Expert insights into the impact of aeropolitics on regional air market integration in ASEAN - Zuan, Haris; Ellis, Darren; Pagliari, Romano (Elsevier, 2023)
By 2015 the Association of Southeast Asian Nations (ASEAN) planned to achieve regional air transport liberalisation through the ASEAN Single Aviation Market (ASAM) to enhance connectivity, economic development and regional integration. However, progress on ASAM has not met initial expectations. To explore the factors influencing air market integration in ASEAN this paper focuses on the concept of aeropolitics, as the literature suggests it plays a significant role in shaping regional integration. A survey (n=50), supported by semi-structured in-depth interviews (n=15), were conducted amongst experts in Southeast Asia to examine the impact of key aeropolitical factors on regional air market integration in ASEAN. Respondents agreed on the importance of factors such as national interest, the influence of political elites with vested interests, regional identity and the involvement of superpowers. By examining experts' perceptions, this paper uncovers complexities and challenges related to the aeropolitical dynamics in ASEAN. Results unearthed a range of key insights and provide the basis for further research and policy development. Centrally, ASEAN is not following the European model with its supranational top-down approach, but rather is incrementally standardising and harmonising air transport across the region based on consensus and mutual interest under the umbrella of the ‘ASEAN way’. Progress for ASAM to date has been more than critics admit, yet less than supporters would like. Within these mixed results lies a story of regional integration that may hold important insights for other regions of the world.
12th International Conference on Air Transport – INAIR 2023, The Future of Aviation – is the Sky the Limit? 15-17 November 2023, Tartu, Estonia
Keywords: ASEAN; aeropolitics; regional intergration; ASEAN way